(untitled) (Research, Society and Development, 2021)
Antimonials are used as chemotherapy for leishmaniasis, but have limited results due to their toxicity and broad resistance already acquired by the parasites. Nanotechnology offers an alternative to reduce these effects through the use of biocompatible nanocarriers, which can be vectorized to the target site. In addition, the redirection of molecules, already developed for the treatment of other pathologies, has the advantage of being already approved for therapy by regulatory agencies. The present study addresses the production of liposomal vesicles containing antimony trioxide (LC Sb2O3), as well as the evaluation of activity against tumor and bacterial cells. We produce liposomes in order of nanometric size, polydispersity index (PDI <0.3), pH value close to physiological (7.2), and zeta potential (anionic). Cytotoxicity was evaluated in 24 and 72 hours, in the HepG2, T98G, and U87MG tumor cell lines, by the method (3-4.5 dimethylthiazole-2.5 diphenyltetrazolium bromide) (MTT). The minimum inhibitory concentration (MIC) was tested on three bacterial strains (American Type Culture Collection – ATCC-Escherichia coli ATCC 35218, Staphylococcus aureus ATCC 29213 and Enterococcus faecalis ATCC 29212) and mandatory (Staphylococcus aureus and Klebsiella pneumoniae). The liposomes were more cytotoxic than Sb2O3 in the free form, for all tested cell lines. This effect was stronger after 72 hours incubation. Antimony trioxide in both free and liposomal forms showed low antibacterial activity. Based on our results, we suggest that liposomes containing antimony trioxide have the potential for the repositioning of drugs addressing anticancer therapy.